NIGERIAN NATIONAL ASSEMBLY AND DOMESTICATION OF TREATIES IN NIGERIA’S FOURTH AND FIFTH ASSEMBLY - NGARA, Christopher Ochanja (Socialscientia: Journal of Social Sciences and Humanities, 2018)
This paper assesses the role of the 4th and 5thNational Assembly in the domestication of treaty instruments in Nigeria. Using both primary and secondary data, it argues that treaty making was an important means by which the National Assembly participated in foreign policy in the 4th and 5th Assembly. However, frequent discord between the executive and the National Assembly, external influence on the Assembly, politicization of treaty Bills and the lack of political will on the part of the legislators were important drawbacks that impacted on the performance of the National Assembly in domesticating treaties. It is recommended that since treaties are indispensable instruments in formalising external relations, the executive should improvise the involvement of the National Assembly at negotiation levels in order to close knowledge and communication gaps between the two arms of government. In the same vein, the National Assembly should expand the scope of public consultation and participation in the process of legislating treaty Bills so that treaties domesticated can be more acceptable to the people.